(untitled) (Research, Society and Development, 2025)
Absenteeism refers to absence from work at times when one should be fulfilling their work commitments. This phenomenon occurs in large quantities in small and medium-sized textile manufacturing companies, mostly involving professionals with low levels of education and who are female. In this sector, working conditions are observed with repetitive tasks, inadequate physical conditions (noise, heat, and dust), and excessive demands that make them exhausting. Thus, the objective was to discuss, through a literature review, the causes of absenteeism in this productive sector. To this end, a bibliographic and descriptive study was carried out with the aid of the Iramuteq software. It was evaluated by descriptive statistics and similarity analysis. The most frequent active terms in the study were: Factor (17); Absenteeism (12); Environment (12) and Employee (12). The relationship between stress in the work environment and a possible contribution to absenteeism was observed. There are numerous factors (ergonomic and occupational) that contribute to risks to the health and safety of employees in companies/organizations in the textile sector. Therefore, it is important to conduct assessments in companies that can make changes and thus improve employee motivation. Therefore, adjustments should be made to the environmental conditions of work (noise, temperature and lighting); the relationship between the tasks and functions performed; financial incentives, career plans, professional training and empathetic relationships in the sector.